ANALISIS INSTRUMEN TES HIGHER ORDER THINKING MATEMATIKA SMP - Sa'idah, Nusrotus; Yulistianti, Hayu Dian; Megawati, Eka (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2019)
This study aims to determine the characteristics of mathematical test instruments seen from the degree of difficulty and different power problems. The instrument developed is the Higher Order Thinking test instrument. The form of this instrument is multiple choice. The sample of this research is students of SMP N 2 Jepara with Mathematics subject. Qualitative studies include material, construction and language aspects. Study quantitatively with the Classical Test Theory approach. In the technique of data analysis, the measured aspect is the validity, reliability, difficulty level, different matter and effectiveness of Distraktor. This question consists of 20 items about multiple choice which refers to taxonomy blomms. Cognitive levels within these items include C4 (evaluation), C5 (Analysis), and C6 (creating). From the results of qualitative analysis indicate that construction, language and material have high or acceptable criteria. The result of analysis with classical test theory using ITEMAN program showed result of item of 50% choice item having good criteria. DOI: 10.22342/jpm.13.1.6619.41-54